Use of wastes from the pulp and paper industry for the remediation of soils degraded by mining activities: Chemical, biochemical and ecotoxicological effects - Alvarenga, Paula (2019)
Fly ash (FA) from biomass combustion and biological sludge (S), both wastes from the pulp and paper industry, were granulated in different proportions (90% FA + 10% S, and 70% FA + 30% S w/w, dry weight basis, dw) and used to recover the functionality of soils affected by mining activities (Aljustrel, Iberian Pyrite Belt), with and without the application of municipal solid waste compost (MSWC). Application doses of both mixtures were 2.5, 5.0 and 10% (w/w, dw). These materials corrected soil acidity to circumneutral values and increased extractable P and K concentrations. A significant increase in soil organic matter (from 0.6 to 0.8–1.5% w/w, dw) and N content (from 0.04 to 0.09–0.12% w/w, dw) was also observed, but only when MSWC was applied. The soil was already heavily contaminated with Cu, Pb and Zn and the application of amendments did not increase their pseudo-total concentrations. The CaCl2 extractable fractions of both Cu and Zn decreased to very low values. The improvement in soil quality, compared to fertilizer only treatment, was further evidenced by the increase in some soil enzymatic activities (dehydrogenase, β-glucosidase and cellulase), with a better response for the granules with the higher proportion of biological sludge, as well as by the decrease in the soil-water extract toxicity towards different organisms (Daphnia magna, Thamnocephalus platyurus, and Pseudokirchneriella subcapitata). Agrostis tenuis germinated and grew during the first month only in the amended pots, but, after that, a considerable phytotoxic effect was evident. This was mainly attributed to salt stress or to some specific ionic toxicity. In conclusion, to establish a long-term plant cover in mining soils amended with biomass ash-based materials, the selection of plants with higher resistance to salinity and/or the stabilization of the amendments, to reduce their soluble salt content, is recommended.